Rational Design of Sustainable Liquid Microcapsules for Spontaneous Fragrance Encapsulation. (17th September 2021) - Mamusa, Marianna; Mastrangelo, Rosangela; Glen, Tom; Murgia, Sergio; Palazzo, Gerardo; Smets, Johan; Baglioni, Piero
Abstract: The high volatility, water‐immiscibility, and light/oxygen‐sensitivity of most aroma compounds represent a challenge to their incorporation in liquid consumer products. Current encapsulation methods entail the use of petroleum‐based materials, initiators, and crosslinkers as well as mixing, heating, and purification steps. Hence, more efficient and eco‐friendly approaches to encapsulation must be sought. Herein, we propose a simple method by making use of a pre‐formed amphiphilic polymer and employing the Hansen Solubility Parameters approach to determine which fragrances could be encapsulated by spontaneous coacervation in water. The coacervates do not precipitate as solids but they remain suspended as colloidally stable liquid microcapsules, as demonstrated by fluorescence correlation spectroscopy. The effective encapsulation of fragrance is proven through confocal Raman spectroscopy, while the structure of the capsules is investigated by means of cryo FIB/SEM, confocal laser scanning microscopy, and small‐angle X‐ray scattering. Abstract : The use of a PEG‐ g ‐PVAc amphiphilic graft copolymer together with hydrophobic fragrances in aqueous medium leads to the spontaneous formation of colloidally stable suspensions of liquid coacervate droplets. Arrows indicate the local turbulences sustaining the spontaneous mixing of the components. The bottom panel shows the confocal Raman microspectroscopy mapping of a multicompartment coacervate droplet with carvone as fragrance.